Ubenimex induces apoptotic and autophagic cell death in rat GH3 and MMQ cells through the ROS/ERK pathway - Wang Y; Pang B; Zhang R; Fu Y; Pang Q (Dove Medical Press, 2019)
Yanjun Wang,1,* Bo Pang,2,* Rui Zhang,1 Yibing Fu,3 Qi Pang1 1Department of Neurosurgery, Shandong Provincial Hospital Affiliated to Shandong University, Jinan 250021, Shandong, People’s Republic of China; 2Department of Neurosurgery, Shandong University, Jinan 250021, People’s Republic of China; 3Department of Obstetrics and Gynecology, Shandong Provincial Hospital Affiliated to Shandong University, Jinan 250021, Shandong, People’s Republic of China*These authors contributed equally to this workCorrespondence: Qi PangDepartment of Neurosurgery, Shandong Provincial Hospital Affiliated to Shandong University, 324 Jingwu Road, Jinan 250021, Shandong Province, People’s Republic of ChinaTel +86 136 1531 6688Email pangqi@sdu.edu.cnYibing FuDepartment of Obstetrics and Gynecology, Shandong Provincial Hospital Affiliated to Shandong University, 324 Jingwu Road, Jinan 250021, Shandong Province, People’s Republic of ChinaTel +86 151 6888 9696Email fuyi_bing@163.comPurpose: Ubenimex, an aminopeptidase N (APN) inhibitor, is widely known for its use as an adjunct therapy for cancer therapy. However, in recent studies, it has also conferred antitumour effects in many cancers, but its anticancer mechanism is largely unknown. This study aims to investigate the specific anticancer activities and mechanisms of ubenimex in GH3 and MMQ cells.Materials and methods: In this study, we investigated the anticancer effects of ubenimex in GH3 and MMQ cells. Cell viability and cell death were assessed by the Cell Counting Kit-8 kit (CCK-8) and a LIVE/DEAD cell imaging kit. Apoptosis and intracellular reactive oxygen species (ROS) generation were assessed by flow cytometry and fluorescence microscopy. Autophagosome formation was detected by transmission electron microscopy, and autophagic flux was measured with mRFP-GFP-LC3 adenoviral transfection. The protein expression level was detected by Western blotting.Results: The results revealed that treatment with ubenimex induced apoptotic and autophagic cell death in GH3 and MMQ cells, which resulted in decreased viability, an increased proportion of apoptotic cells, and autophagosome formation. Further experiments showed that ubenimex induced ROS generation and activated the ROS/ERK pathway. The ROS scavenger NAC could attenuate ubenimex-induced apoptosis and autophagy.Conclusion: Our studies revealed that ubenimex exerted anticancer effects by inducing apoptotic and autophagic cell death in GH3 and MMQ cells, rendering it a possible effective adjunctive therapy for pituitary treatment.Keywords: pituitary, ubenimex, autophagy, apoptosis, ROS